N1-methyladenosine (m1A) regulation associated with the pathogenesis of abdominal aortic aneurysm through YTHDF3 modulating macrophage polarization - Wu, Yihao; Jiang, Deying; Zhang, Hao; Yin, Fanxing; Guo, Panpan; Zhang, Xiaoxu; Bian, Ce; Chen, Chen; Li, Shuixin; Yin, Yuhan; Böckler, Dittmar; Zhang, Jian; et al. (Frontiers in Cardiovascular Medicine, 2022)
ObjectivesThis study aimed to identify key AAA-related m1A RNA methylation regulators and their association with immune infiltration in AAA. Furthermore, we aimed to explore the mechanism that m1A regulators modulate the functions of certain immune cells as well as the downstream target genes, participating in the progression of AAA.MethodsBased on the gene expression profiles of the GSE47472 and GSE98278 datasets, differential expression analysis focusing on m1A regulators was performed on the combined dataset to identify differentially expressed m1A regulatory genes (DEMRGs). Additionally, CIBERSORT tool was utilized in the analysis of the immune infiltration landscape and its correlation with DEMRGs. Moreover, we validated the expression levels of DEMRGs in human AAA tissues by real-time quantitative PCR (RT-qPCR). Immunofluorescence (IF) staining was also applied in the validation of cellular localization of YTHDF3 in AAA tissues. Furthermore, we established LPS/IFN-γ induced M1 macrophages and ythdf3 knockdown macrophages in vitro, to explore the relationship between YTHDF3 and macrophage polarization. At last, RNA immunoprecipitation-sequencing (RIP-Seq) combined with PPI network analysis was used to predict the target genes of YTHDF3 in AAA progression.ResultsEight DEMRGs were identified in our study, including YTHDC1, YTHDF1-3, RRP8, TRMT61A as up-regulated genes and FTO, ALKBH1 as down-regulated genes. The immune infiltration analysis showed these DEMRGs were positively correlated with activated mast cells, plasma cells and M1 macrophages in AAA. RT-qPCR analysis also verified the up-regulated expression levels of YTHDC1, YTHDF1, and YTHDF3 in human AAA tissues. Besides, IF staining result in AAA adventitia indicated the localization of YTHDF3 in macrophages. Moreover, our in-vitro experiments found that the knockdown of ythdf3 in M0 macrophages inhibits macrophage M1 polarization but promotes macrophage M2 polarization. Eventually, 30 key AAA-related target genes of YTHDF3 were predicted, including CD44, mTOR, ITGB1, STAT3, etc.ConclusionOur study reveals that m1A regulation is significantly associated with the pathogenesis of human AAA. The m1A “reader,” YTHDF3, may participate in the modulating of macrophage polarization that promotes aortic inflammation, and influence AAA progression by regulating the expression of its target genes.